The Agency of Students in the PGSD Study Program in the AI Era: A Philosophical Framework for the Acceptance of Technology and Micro Credentials in Arts and Culture - Yona Syaida Oktira; Zelhendri Zen; Jasrial Jasrial; Ahmad Fauzan (The Future of Education Journal, 2025)
The development of artificial intelligence (AI) and the micro-credential ecosystem has fundamentally transformed the landscape of higher education. Students in the Primary School Teacher Education (PGSD) program at Nahdlatul Ulama University of West Sumatra are no longer positioned merely as prospective teachers who implement the curriculum, but as subjects with agency who must possess the capacity to act autonomously, reflectively, and responsibly in interpreting, selecting, and using technology, including AI and micro-credentials in the field of arts and culture. This study aims to construct a philosophy of education framework to understand and strengthen the agency of PGSD students in embracing technology and arts and culture micro-credentials in the current AI-driven digital era. This study employs a qualitative approach using a narrative literature review and philosophical analysis integrated with: (1) the concept of agency in Bandura’s social cognitive theory; (2) Biesta’s three domains of educational purposes (qualification, socialization, and subjectification); (3) technology acceptance models; (4) Indonesian micro-credential policy and practices; and (5) the position of arts and culture courses within the PGSD curriculum. The findings indicate that the acceptance of AI and micro-credentials cannot be reduced to purely technical issues such as ease of use and perceived usefulness, but must be situated within an ethical philosophical framework concerning the kind of elementary school teachers students aspire to become. This paper proposes a conceptual model of “PGSD Student Agency in the AI Era” that connects self-efficacy beliefs, educational values, perceptions of AI, and motivation to participate in arts and culture micro credentials. Practical implications include the design of a PGSD curriculum that positions arts and culture as a practical space for exercising agency, the critical integration of AI-based micro-credentials, and pedagogical strategies that foster ethical and reasonable digital literacy in the use of digital technologies.